Different Roles of the Left and Right Ventrolateral Prefrontal Cortex in Cognitive Reappraisal: An Online Transcranial Magnetic Stimulation Study - Cheng, Si; Qiu, Xiufu; Li, Sijin; Mo, Licheng; Xu, Feng; Zhang, Dandan (Frontiers in Human Neuroscience, 2022)
The ventrolateral prefrontal cortex (VLPFC) plays a pivotal role in cognitive reappraisal. Previous studies suggested a functional asymmetry of the bilateral VLPFC, but the evidence is still insufficient during cognitive reappraisal. In this study, we applied online single-pulse transcranial magnetic stimulation (spTMS) to investigate the causal and distinct roles of the left and right VLPFC in reappraisal. Participants were instructed to reappraise (down-regulate) or attend to pictures depicting social exclusion scenarios while the spTMS was applied over the left or right VLPFC of participants’ brain. The results showed that spTMS over either the left or the right VLPFC would increase reappraisal difficulty. Meanwhile, the outcome of reappraisal (measured by self-reported negative feelings) was significantly deteriorate when the right (but not the left) VLPFC was temporally interrupted by spTMS, while the verbal fluency during oral reporting of reappraisal strategy was significantly reduced when the left (but not the right) VLPFC was interrupted by spTMS. Taken together, these findings provide causal evidence for the involvement of left and right VLPFC with distinct roles: while the left VLPFC is responsible for linguistic especially semantic process of generating and selecting appraisals according to the goal of emotion regulation, the right VLPFC plays a critical role in inhibiting inappropriate negative emotion and thoughts generated by the affective scenarios. These findings deepen our understanding of the neurocognitive mechanism of emotion regulation.